Juridical Analysis of Criminal Acts Defamation and Hoaxes Through Social Media Against Corporations in the Perspective of the ITE Law: english - Kadek Wahyudi Saputra; Suparji; Anis Rifai (Faculty of Law, University of Mataram, 2024)
This study aims to analyze the legal aspects related to crime and the implications for corporations as legal subjects. The research method used a normative juridical approach concerning various related laws and regulations, court decisions, and opinions of legal experts. The analysis results show that criminal acts of defamation and spreading hoaxes through social media can be prosecuted by the articles governing insult and defamation and spreading false information in the ITE Law. The implications for corporations are significant because defamation and the spread of hoaxes can damage a company's reputation and affect relationships with customers, business partners, and other stakeholders. Therefore, corporations need to understand legal obligations and responsibilities regarding content produced by internal and external parties related to the company. This research proposes the need for more proactive prevention efforts on the part of corporations, such as developing guidelines for the use of social media and training for employees, as well as increasing understanding of the legal implications of social media activities. In addition, updating or revising the ITE Law also needs to be considered to accommodate the dynamics of the development of social media and information technology, which are constantly changing.